The discussion of risk in German surgical clinical practice guidelines: A qualitative review - Mclennan, Stuart; Jansen, Carolin; Buyx, Alena (Innovative Surgical Science, 2021)
Clinical practice guidelines (CPGs) have a potentially important role regarding the assessment and communication of the risks of perioperative complications. This study aimed to (1) examine the content of German surgical CPGs in relation to surgical risks and (2) provide baseline results for future research in order to assess the development of surgical CPGs in Germany in relation to this issue. In November 2015, all German surgical CPGs that provide guidance regarding illnesses that can be treated with a surgical procedure were collected from the websites of the German umbrella organisation of medical professional associations and the German Association for Cardiology. Data collection retrieved 230 CPGs of which 214 were included in the final analysis. The analysis identified four different groups: 1) 5% (10/214) of guidelines did not discuss "risks"or "complications"at all; 2) 21% (44/214) of guidelines discussed general risks that are not related to surgical complications; 3) 35% (76/214) of guidelines discussed surgical complications and often discussed their likelihood in terms of "high risk"or "low risk", but did not provide numeric estimates and 4) 39% (84/214) of guidelines discussed specific surgical risks and also provided numerical risk estimates. Guidelines with higher methodological quality more frequently included numerical risk estimates. It is positive that the vast majority of German surgical CPGs address the issue of risks. However, it would be helpful if more German surgical CPGs provide explicit and evidence-based estimates and recommendations relating to the surgical risk to support surgeons in providing high-quality care and to meet their ethical obligations to patients.
CRIS-Team Scopus Importer:2023-03-08
Keywords: clinical practice guideline; risks; surgery